2014
DOI: 10.1109/tdei.2014.003856
|View full text |Cite
|
Sign up to set email alerts
|

Prebreakdown current and dc breakdown strength of alumina-filled poly(ethylene-co-butyl acrylate) nanocomposites: Part I - breakdown strength

Abstract: Dielectric breakdown strength of poly (ethylene-co-butyl acrylate) (EBA)nanocomposites filled with spherical alumina particles was studied as a function of particle coating, moisture content and the effective specific surface area. Two kinds of alumina nanoparticles were used: NA (25 nm in diameter) or ND (45 nm in diameter). The particles were either unmodified or surface-treated with aminopropyltriethoxy silane or octyltriethoxy silane. Two different relative humidities of air were used for conditioning the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
3
9
0
Order By: Relevance
“…3) show disrupted spherulitic textures, which are suggestive of enhanced polymer nucleation, and contain Al2O3 inclusions ranging in size from ~50 nm to 5 μm. In thermosetting epoxy/alumina systems, both good [14,16] and poor [17] alumina particle dispersions have been reported, whilst another study using the more relevant thermoplastic host polymer ethylene-co-butyl acrylate [22] indicated very similar aggregated morphologies to those reported here.…”
Section: A Composition and Morphologysupporting
confidence: 79%
See 2 more Smart Citations
“…3) show disrupted spherulitic textures, which are suggestive of enhanced polymer nucleation, and contain Al2O3 inclusions ranging in size from ~50 nm to 5 μm. In thermosetting epoxy/alumina systems, both good [14,16] and poor [17] alumina particle dispersions have been reported, whilst another study using the more relevant thermoplastic host polymer ethylene-co-butyl acrylate [22] indicated very similar aggregated morphologies to those reported here.…”
Section: A Composition and Morphologysupporting
confidence: 79%
“…Previously, silica based systems were studied by the authors [37] and it was found that the dielectric properties were highly sensitive to conditioning and several papers indicate that this may also be the case for alumina [22,23]. Drying the nanocomposites led to electrical properties similar to that of the host polymer, whereas absorbed water always had a detrimental effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, increases in AC breakdown strength in epoxy/alumina systems have been reported [16,17] while, in another study [18], absorbed water was reported to reduce the electrical breakdown strength of a series of alumina/ethylene-co-butene acrylate composites. Other notable papers on alumina [19,20] and aluminum nitride [21,22] focus on their improved thermal conductivity, which could potentially increase short term overload ratings if such composites were to be employed in a high voltage cable system [23].…”
Section: Introductionmentioning
confidence: 73%
“…Hui et al [34] considered the effect of moisture on a series of XLPE/silica nanocomposites and showed a progressive reduction in breakdown strength with increasing moisture content. Finally, Jaeverberg et al [35] compared the breakdown strength of epoxy/alumina nanocomposites exposed to dry and humid conditions and found that humid conditions significantly reduced the breakdown strength. Thus, all the available work seems to indicate a reduction in the breakdown strength of nanocomposites that contain water, in agreement with our findings.…”
Section: Breakdownmentioning
confidence: 99%